Penatalaksanaan Mukokel dengan Mikro marsupialisasi pada Pasien Anak (Laporan Kasus) - Deviyanti Pratiwi; Arianne Dwimega (Jurnal Kedokteran Gigi Terpadu, 2021)
Background : Mucocele can be caused by mucus extravasation and mucus retention phenomenon. Mucocele on the lower lip due to mechanical trauma, such as the habit of biting the lower lip, causing a bulge that causes discomfort. Mucoceles are often found in pediatric and adolescent patients. Micro marsupialization is a non-surgical procedure that can be performed on pediatric patients . This procedure is simpler to perform, minimally invasive, and well tolerated by the patient.. Case report : A 6-year-old boy came with complaints of a red bulge with bluish edges, 4 mm in diameter on the lower lip that caused discomfort. The bulge has only been noticed since 2 weeks ago. Patient has a habit of biting his lower lip so that the bulge gets bigger. Patient has a history of fear to surgery and showed anxiety during examination. . Micro-marsupialization was performed and patient was instructed to eliminate the habit of biting lower lip and to maintain his oral health. Conclusion : Micro marsupialization in mucocele cases shows good results of treatment in pediatric patients who have a history of fear to surgery.